Design and Construction of a Plastic Bottle Waste Collector Integrated with a Microcontroller-Based IoT System - M Furqan; Misbahul Jannah; Taufiq Taufiq; Salahuddin Salahuddin; Dedi Fariadi (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
Automatic garbage cans use ultrasonic sensors to automate manual garbage cans to make it easier for people to dispose of garbage and increase awareness of environmental cleanliness. Automatic bins using ultrasonic sensors are controlled via microcontrollers. In the design of Plastic Bottle Waste Collection Equipment Integrated with a Microcontroller-Based IoT System, several stages of research were carried out: literature study, system design and implementation, and system testing. The process of Plastic Bottle Waste Collection Equipment Integrated with a Microcontroller-Based IoT System is that when a person puts plastic bottle waste into the plastic bottle waste collection device, the load cell will weigh the weight of the bottle waste. Next, the data is processed by Arduino Uno, and then I press the push button to print the generated data. Press the push button II to drop the plastic bottle waste into the garbage bin. From the results of testing the weight of plastic bottle waste using a load cell, it can be concluded that it works well. And the difference in the accuracy of the weight of plastic bottle waste using a load cell with a digital scale of 0.01 > 0.05 Kg.